PENGEMBANGAN MODEL PEMBELAJARAN NHT (NUMBERED HEADS TOGETHER) BERBASIS OUTDOOR STUDY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SMA KELAS X PADA MATERI POKOK SISTEM PERSAMAAN DAN PERTIDAKSAMAAN - Marfuah, Iim; Mardiyana, Mardiyana; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of the research were: (1) to yield valid, efficient, practical and effective learning model for equation and inequality system; (2) to know which students had better the learning achievement of mathematics using outdoor study-based NHT or NHT learning models; (3) to know which students had better learning achievement, the students with high or those with moderate or those with low social intelligence; (4) to know which for students with high social intelligence, moderat social intelligence and low social intelligence, outdoor study-based NHT had better learning achievement than NHT learning model; (5) to know which students had better learning achievement, outdoor study-based NHT or NHT learning model, in each level of social intelligence. The development of learning model was conducted referring to R&D procedure suggested by Borg & Gall. The result of development constituted the procedure/syntax of outdoor study-based NHT learning model. For effectiveness test, this research was a quasi-experimental research with a 2Ã3 factorial design. The instrument employed to collect the data was mathematics learning achievement test and student social intelligence questionnaire. Based on hypothesis testing, it can be concluded as follows. (1) The result of development constituted the procedure/syntax of outdoor study-based NHT were valid, efficient, practical and effective learning model with some game or activity such us ringball for SPLDV game, ringball for SPLDV game, to guess length and wide, inequality project and estafed. (2) The studentsâ mathematics learning achievement in outdoor study-based NHT learning model was better than that in NHT. (3) The students with high social intelligence had mathematics learning achievement better than those with either moderate or low one, and those with moderate had mathematics learning achievement better than those with low one. (4). In outdoor study-based NHT learning model, the students with high social intelligence had mathematics learning achievement as same as those with moderate one, and those with either high or moderate social intelligence had mathematics learning achievement better than those with low one. In NHT learning model, the students with high social intelligence had mathematics learning achievement better than those with either moderate or low one, and those with moderate one had mathematics learning achievement as same as those with low one. (5) The students with high social intelligence in outdoor study-based NHT learning model provided the result (product) as same as those in NHT learning model. The students with moderate social intelligence in outdoor study-based NHT learning model provided the result better than those in NHT learning model. The students with low social intelligence in outdoor study-based NHT learning model provided the result as same as those in NHT learning model.Keywords: NHT (Numbered Heads Together), Outdoor Study, Student Social Intelligence